Improving Students’ Ability at Memorizing Vocabulary Through Implementation of Guessing Game Strategy at MTs AL Washliyah Batang Serangan - Nazli Fahada (Journal of Classroom Action Research, 2022)
Vocabulary is an important element in a language ,all the words known and used by a particular person. Vocabulary is the basic need that has to be mastered by the students themselves. They will find it difficult to speak up without having many vocabularies as it is difficult to memorize. In teaching vocabulary  teacher should use many strategy to make the students understand the meaning and how to voice the word such asking and answering, using media, etc. As far as its known, there are many strategy that use in teaching learning process. One of them is guessing game strategy that use by the teacher in teaching. The aims of this research are to find out the students’ ability to memorizing vocabulary speech when taught by guessing game strategy, improving the students’ ability at memorizing vocabulary by using guessing game strategy. The subject of this research is MTs Al Washliyah Batang Serangan. The subject  was  68 students that consist of 2 classes, they are VIII A  that consist of 35 students and, the technique of collecting data were interview, document, observation, written test. the technique of analyzing data Presenting the data and data Reduction. After the data were analyzed, it showed that in  ( pretest )  the students’ ability at memorizing vocabulary of MTs Al Washliyah Batang Serangan by guessing game strategy  got the mean 2,86 % and cycle 1 ( postest 1 )  got the mean 57.14 %. So, it can be concluded that there is an improvement of the students’ ability at memorizing vocabulary by using guessing game strategy. Keywords  : Guessing game strategy , memorizing vocabulary .